2002
DOI: 10.1128/iai.70.10.5547-5555.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Immunization Elicits Antigen-Specific Protective Immune Responses and Decreases Disease Severity inTrypanosoma cruziInfection

Abstract: Immunity to Trypanosoma cruzi requires elicitation of humoral and cell-mediated immune responses to extracellular trypomastigotes and intracellular amastigotes. In this study, the effectiveness of the T. cruzi trans-sialidase family (ts) genes ASP-1, ASP-2, and TSA-1 as genetic vaccines was assessed. Immunization of mice with plasmids encoding ASP-1, ASP-2, or TSA-1 elicited poor antigen-specific cytotoxic-T-lymphocyte (CTL) activity and T. cruzi-specific antibody responses. Codelivery of interleukin-12 and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
91
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 45 publications
10
91
1
3
Order By: Relevance
“…To determine the role of immunisation in reducing chronic phase disease symptoms, a number of experiments using different animal models must be performed. In many of the models described above, tissue inflammation and parasitism in the late chronic phase were significantly reduced following prophylactic vaccination (Garg & Tarleton 2002, Vasconcelos et al 2004, Araújo et al 2005. Therefore it is possible that prophylactic vaccinations indeed halt the development of the chronic phase immunopathologies.…”
Section: As Shown Inmentioning
confidence: 99%
“…To determine the role of immunisation in reducing chronic phase disease symptoms, a number of experiments using different animal models must be performed. In many of the models described above, tissue inflammation and parasitism in the late chronic phase were significantly reduced following prophylactic vaccination (Garg & Tarleton 2002, Vasconcelos et al 2004, Araújo et al 2005. Therefore it is possible that prophylactic vaccinations indeed halt the development of the chronic phase immunopathologies.…”
Section: As Shown Inmentioning
confidence: 99%
“…They demonstrated that the genes encoding ASP-1, ASP-2 and LYT1 could provide a high degree of protective immunity against experimental infection Tarleton 2002 andFralish andTarleton 2003).…”
Section: Trypanosoma Cruzimentioning
confidence: 99%
“…An alternative vaccination approach has been to immunize mice with DNA, where the protein product is produced in vivo from the plasmid DNA. This approach has been used successfully against both protozoan (7,16,29) and helminth (10,46,53,54) infections resulting in measurable immune responses, some of which mediate protective immunity.…”
mentioning
confidence: 99%